Cadmium Selenide Polymer Microfiber Saturable Absorber for Q-Switched Fiber Laser Applications - Rosol, Ahmad Haziq Aiman; Rahman, Husna Abdul; Ismail, Ezzatul Irradah; Irawati, Ninik; Jusoh, Zulzilawati; Latiff, Anas Abdul; Harun, Sulaiman Wadi (IOP Publishing, 2017)
We demonstrate the generation of a Q-switching pulse train in an erbium-doped fiber laser (EDFL) cavity using a newly developed cadmium selenide (CdSe) based saturable absorber (SA). The SA is obtained by embedding CdSe nanomaterials into a polymethyl methacrylate (PMMA) microfiber. It is incorporated into an EDFL cavity to generate a Q-switched laser operating at 1533.6 nm. The repetition rates of the produced pulse train are tunable within 3764 kHz as the pump power is varied from 34mW to 74mW. The corresponding pulse width reduces from 7.96 μs to 4.84 μs, and the maximum pulse energy of 1.16 nJ is obtained at the pump power of 74mW.